Analisis Hubungan Strategi Koping Keluarga dengan Kualitas Hidup Lansia Gangguan Kognitif Ringan (Mild Cognitive Impairment) di Wilayah Pinggiran Sungai Kapuas Banjar Serasan Kota Pontianak - Dodik Limansyah; Masmuri; Fitriah (MES Bogor, 2025)
The increase in life expectancy among the elderly is, on one hand, a positive development, but on the other hand, it can lead to new social challenges, particularly concerning elderly care and welfare. Changes experienced by the elderly, such as reduced income due to retirement, physical changes, and communication difficulties, also impact their quality of life. The quality of life for the elderly is not solely measured by general satisfaction but encompasses various dimensions, including physical, psychological, social, and environmental factors. From an Islamic perspective, caring for and showing attention to the elderly is highly encouraged, with an emphasis on the importance of emotional and social support. This study aims to analyze the relationship between family coping strategies and the quality of life of elderly individuals with mild cognitive impairment in the working area of the Banjar Serasan Health Center, East Pontianak. The research employed a descriptive correlative design with a cross-sectional approach. The study involved 50 elderly participants aged 60 years and above, selected through screening using the MMSE (Mini-Mental State Examination) instrument. The findings of the study concluded that family coping strategies play a crucial role in enhancing the quality of life for elderly individuals with mild cognitive impairment. Statistical analysis revealed a significant value (p = 0.000), result indicating a relationship between family coping strategies and the quality of life of the elderly with mild cognitive impairment. The correlation coefficient value of 0.663 suggests a strong relationship.